2007
DOI: 10.1007/bf02698015
|View full text |Cite
|
Sign up to set email alerts
|

Excess calcium increases bone zinc concentration without affecting zinc absorption in rats

Abstract: We examined zinc (Zn) metabolism in rats given diets containing excess calcium (Ca). Rats were given phytate-free diet containing 5 g Ca/kg (control), 12.5 g Ca/kg, or 25 g Ca/kg for 4 wk in Experiment 1. The dietary treatment did not affect Zn concentration in the plasma, testis, kidney, spleen and liver; however, Zn concentration in the femur and its cortex was significantly higher in rats given diet containing 25 g Ca/kg than in other rats. Rats were given phytate-free diet containing 5 g Ca /kg or 25 g Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…The effect of excess Ca on Zn absorption remains controversial: our results are in disagreement with those reported in other studies that showed that an excess Ca diet either did not affect (Takasugi et al, 2007) or decreased (Dursun & Aydogan, 1994;Wood & Zheng, 1997) the absorption of Zn. However, in our study, the supplementation of Ca in the diet increased the nutritive utilization of Zn in both in the control and the anaemic rats for the goat milk diet and in the control rats for the cow milk diet.…”
Section: Digestive and Metabolic Utilization Of Zncontrasting
confidence: 83%
See 1 more Smart Citation
“…The effect of excess Ca on Zn absorption remains controversial: our results are in disagreement with those reported in other studies that showed that an excess Ca diet either did not affect (Takasugi et al, 2007) or decreased (Dursun & Aydogan, 1994;Wood & Zheng, 1997) the absorption of Zn. However, in our study, the supplementation of Ca in the diet increased the nutritive utilization of Zn in both in the control and the anaemic rats for the goat milk diet and in the control rats for the cow milk diet.…”
Section: Digestive and Metabolic Utilization Of Zncontrasting
confidence: 83%
“…Dursun and Aydogan (1994) showed that a diet containing 20 g Ca kg À1 decreased the true absorption of Zn in rats. Takasugi et al, (2007) showed that excess Ca of 25 g kg À1 diet, did not affect the true absorption of Zn and its endogenous excretion.…”
Section: Introductionmentioning
confidence: 97%
“…The reduction of Mg absorption was unlikely to be enough for lowering plasma Mg concentration in the HC group in the present experiment. Femoral Zn concentration increased in the HC rats, which was supported by other reports indicating that excess Ca as carbonate increased the Zn concentration in bone [5,6,7]. Planells et al [8] reported that Mg deficiency increased bone Zn concentration in rats.…”
Section: Discussionsupporting
confidence: 64%
“…Although excess Ca as carbonate decreases bone Zn concentration in animals given high phytate diets through suppressing Zn absorption [4], Takasugi et al [5] indicated that excess Ca as carbonate increased bone Zn concentration without affecting true absorption of Zn in rats given a phytate-free diet. Furthermore, some other reports also showed that excess Ca as carbonate increased bone Zn concentration and decreased renal Zn concentration in rats given a phytate-free diet [6,7].…”
mentioning
confidence: 99%
“…These foods are also characterized by high phosphorous and calcium contents (Simova, Ivanov, & Simov, 2008). To date, the effect of calcium on zinc absorption has been intensely debated: some authors have suggested that it decreases zinc bioavailability (Dursun & Aydogan, 1994;Hunt, 2003;Maret & Sandstead, 2006;Walter, Rimbach, Most, & Pallauf, 2000), while others state that it has no influence (Hallberg, Brune, Erlandsson, Sandberg, & Rossander-Hultén, 1991;Lönnerdal, 2000;Takasugi, Matsui, Omori, & Yano, 2007) or even a stimulatory effect (Diaz-Castro, Alferez, Lopez-Aliaga, Nestares, & Campos, 2009). A further property that makes milk-based products like yoghurt and cheese the logical choice for zinc fortification is their low pH (Rosado, 2003).…”
Section: Introductionmentioning
confidence: 97%